The Intersection of Corporate Social Responsibility (CSR), Firm Performance, and Clinical Psychology - Samuel Ejiro Uwhejevwe-Togbolo; Victoria Omenebele Kaizar; Sunny Oteteya Temile; Festus Elugom Ubogu; Prince Efanimjor; A. A. Okwoma (Review of Ethics in Sustainable Finance and Accounting, 2025)
CSR is a firm’s dedication to the environmental and social responsibility of business practices. As businesses become more aware of their social and environmental responsibilities, CSR has become more and more important in today’s firm operations. Firms have begun introducing workplace wellness programs, counselling services, and stress management workshops to support employee well-being. These initiatives align with clinical psychology principles, emphasising resilience, ethical behaviour, and interpersonal dynamics. The study The study adopts a quantitative research design to explore the intersection of CSR, FP, and clinical psychology. The study population comprise of the 108 non-financial firms quoted in the Nigerian Exchange Group (NGX) as at December 2024. A purposive sampling technique is employed to select 85 respondents who have direct experience with CSR practices and mental health interventions in their organizations. The study data is collected through a structured questionnaires designed to measure respondents' perceptions of CSR initiatives, FP, and clinical psychology-related programs. The results of the study amongst others indicate that CSR initiatives focusing on employee well-being contribute to productivity and stakeholder trust. The study concluded that, the intersection of CSR, firm performance, and clinical psychology principles reveals promising trends. CSR and mental health-focused programs guided by psychological insights will positively impact employee well-being, productivity, ethical leadership, stakeholder trust, and sustainability. It was recommended in the study that, firms should prioritize psychological well-being when designing and implementing CSR initiatives to fully realize their potential benefits.